2005
DOI: 10.1038/sj.bjc.6602417
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor acts as an osteolytic factor in breast cancer metastases to bone

Abstract: Vascular endothelial growth factor (VEGF) is a proangiogenic cytokine that is expressed highly in many solid tumours often correlating with a poor prognosis. In this study, we investigated the expression of VEGF and its receptors in bone metastases from primary human breast tumours and further characterised its effects on osteoclasts in vitro. Breast cancer metastases to bone were immunohistochemically stained for VEGF, its receptors VEGFR1 and 2 (vascular endothelial growth factor receptor 1 and 2), demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 32 publications
(27 reference statements)
4
41
1
1
Order By: Relevance
“…Increased VEGF level was also associated with biochemical markers of osteoclastic activity and bone matrix degradation, which is in agreement with a recent study showing high that VEGF stimulates osteoclastic differentiation in vitro (Aldridge et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Increased VEGF level was also associated with biochemical markers of osteoclastic activity and bone matrix degradation, which is in agreement with a recent study showing high that VEGF stimulates osteoclastic differentiation in vitro (Aldridge et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…The key angiogenic factor vascular endothelial growth factor-A (VEGF-A) is produced in metastatic bone lesions (9)(10)(11). Blocking VEGF-A in breast cancer bone metastasis reduces osteolytic lesions (12).…”
Section: Introductionmentioning
confidence: 99%
“…VEGFR1 positive haematopoietic progenitor cells are recruited to sites of future metastasis (88). VEGF receptors are expressed by breast cancer cells as well as osteoclasts and osteoclast precursors, and VEGF expression correlates to increased tumour size and grade in humans (89). In addition, we have shown that breast cancer cells secrete factors that support the subsequent attachment of breast cancer cells acting at least in part through -secretase-mediated Notch signalling (20).…”
Section: Homing Of Breast Cancer Cells To Bone 41 Creation Of the Prmentioning
confidence: 99%